Analisa Interaksi Pengguna Media Sosial Perusahaan Sekuritas di Indonesia Saat Covid-19 menggunakan Social Network Analysis (Studi Kasus: Indopremier dan Bursa Efek Indonesia) - Della Diniyati; Agung Triayudi; Ira Diana Sholihati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The development of information technology, especially social media users, is increasing. Many securities companies make use of technology so that users can make various transactions and search for information digitally. This can be used in online marketing strategies and information dissemination, one of which is Twitter. Users can disclose known information and this information is User Generated Content (UGC), which is the track record left behind. Twitter user interaction analysis can provide information that supports various business decisions, such as customer engagement. This research takes advantage of the Covid-19 phenomenon in which the stock market has experienced a global downturn. The purpose of this study is to determine the level of awareness and identify customer engagement from the results of the implementation of Social Customer Relationship Management (SCRM) by the company. This study uses the Social Network Analysis (SNA) method, with secondary data in the form of tweets of Twitter user interactions regarding 2 securities companies, IndoPremier, and the Indonesia Stock Exchange. The result is that IndoPremier is a securities company that is superior in informing optimal customer engagement through the implementation of SCRM.